Professional marketing aspects of Unilever Bangladesh Limited : Gulshan branch - Choudhury, Ruhama Tasnim (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.